(untitled) (Third Sector Social Economic Review, 2025)
This study aims to analyze the structure, practices, and market dynamics of cargo (marine) insurance in Türkiye. Cargo insurance, a key branch of insurance literature, provides coverage for goods transported by road, sea, air, or rail against potential losses incurred during transit (General Conditions of Cargo Insurance, 1953). In the Turkish context, the scope and implementation of cargo insurance must be evaluated together with relevant regulations, market actors, premium structures, types of coverage, and tariff formation. The purpose of this study is to offer a comprehensive empirical assessment of cargo insurance in Türkiye, thereby addressing a gap in the existing literature and developing practical recommendations for policymakers, insurers, and logistics sector stakeholders. Using monthly data for the period 2014 – 2024, the relationships between cargo insurance (marine) indicators and macroeconomic variables were examined. ADF unit root tests indicated that all variables are stationary at first differences, while the Johansen cointegration test confirmed the existence of a long-run relationship among the variables. Granger causality analysis revealed that foreign trade volume, interest rates, and the average exchange rate are significant determinants of cargo insurance premium production. Sectoral data further showed a stable increase in the number of policies and a sharp rise in premium production and technical profits between 2019 and 2024. Overall, the findings demonstrate that cargo insurance in Türkiye is highly sensitive to foreign trade and financial indicators, functioning as a financial mechanism that supports economic activity and contributes to economic growth.